Income inequality in Colombia: empirical evidence in the period 1990-2018 - Salazar Garcia, Juan Sebastian (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This paper studies and describes income inequality in Colombia and its average schooling, using cross-sectional data from different specialized databases for the period 1990 to 2018, in order to highlight recentdynamics of inequality reduction. These dynamics go against the trend of gradual increase in income inequality that developed economies have experienced since 1970. The cross-data show that the apparentimprovement in the average educational level in Colombia, used as a proxy variable for the average level of human capital, is concomitant with the reduction of income inequality.